Nanostructures of diamond, graphene oxide and graphite inhibit CYP1A2, CYP2D6 and CYP3A4 enzymes and downregulate their genes in liver cells - Strojny B (Dove Medical Press, 2018)
Barbara Strojny,1 Ewa Sawosz,1 Marta Grodzik,1 Sławomir Jaworski,1 Jarosław Szczepaniak,1 Malwina Sosnowska,1 Mateusz Wierzbicki,1 Marta Kutwin,1 Sylwia Orlińska,1 André Chwalibog2 1Division of Nanobiotechnology, Warsaw University of Life Sciences, Warsaw, Poland; 2Department of Veterinary and Animal Sciences, University of Copenhagen, Frederiksberg, Denmark Introduction and objective: Currently, carbon nanostructures are vastly explored materials with potential for future employment in biomedicine. The possibility of employment of diamond nanoparticles (DN), graphene oxide (GO) or graphite nanoparticles (GN) for in vivo applications raises a question of their safety. Even though they do not induce a direct toxic effect, due to their unique properties, they can still interact with molecular pathways. The objective of this study was to assess if DN, GO and GN affect three isoforms of cytochrome P450 (CYP) enzymes, namely, CYP1A2, CYP2D6 and CYP3A4, expressed in the liver. Methods: Dose-dependent effect of the DN, GO and GN nanostructures on the catalytic activity of CYPs was examined using microsome-based model. Cytotoxicity of DN, GO and GN, as well as the influence of the nanostructures on mRNA expression of CYP genes and CYP-associated receptor genes were studied in vitro using HepG2 and HepaRG cell lines. Results: All three nanostructures interacted with the CYP enzymes and inhibited their catalytic activity in microsomal-based models. CYP gene expression at the mRNA level was also downregulated in HepG2 and HepaRG cell lines. Among the three nanostructures, GO showed the most significant influence on the enzymes, while DN was the most inert. Conclusion: Our findings revealed that DN, GO and GN might interfere with xenobiotic and drug metabolism in the liver by interactions with CYP isoenzymes responsible for the process. Such results should be considered if DN, GO and GN are used in medical applications. Keywords: carbon nanostructures, nanoparticles, cytochrome P450, microsomes, liver